One mRNA Vaccine to Rule Them All (Molecular Medicine Communications, 2022)
Vaccines for seasonal influenza do not confer protection against the pandemic strains of the influenza virus. Due to the uncertainty in identifying which viral strain of influenza may cause the next pandemic, it is challenging to develop pre-pandemic vaccines. A nucleoside-modified messenger RNA (m-RNA) encapsulated in a lipid nanoparticle that codes for hemagglutinin protein for all 20 strains of both influenza A and influenza B virus were formulated by Arevalo and colleagues. In mice and ferrets administered with this multivalent vaccine, cross-reactive and subtype-specific antibodies targeting all 20 encoded antigens were developed. The immunized mice and ferrets exhibited strong resistance once challenged with matched and mismatched viral strains. The antibodies developed were in part responsible for conferring this protection. Their studies indicate that mRNA vaccines can provide protection against antigenically variable viruses by inducing antibodies against multiple antigens simultaneously. Science (2022) DOI: 10.1126/science.abm0271.